2017
DOI: 10.1186/s13000-017-0643-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic pancreas in the omphalomesenteric duct remnant in a 9-month-old girl: a case report and literature review

Abstract: BackgroundHeterotopic pancreas most commonly occurs in the upper gastrointestinal tract of adults, usually as an incidental finding. It seldom occurs at the umbilicus, and even rarely in the pediatric age group.Case presentationHere we present a case of heterotopic pancreatic tissue in the omphalomesenteric duct remnant of a 9-month-old baby girl. She presented with redness at the base of the umbilicus associated with occasional mild wetness. A urachal fistula was suspected by ultrasound. Histology from subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…Zhao et al . reviewed 18 patients with ectopic pancreas at the umbilicus and reported that most of them presented with umbilical discharge . A definitive preoperative diagnosis is difficult to obtain, because ectopic pancreas is hard to detect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al . reviewed 18 patients with ectopic pancreas at the umbilicus and reported that most of them presented with umbilical discharge . A definitive preoperative diagnosis is difficult to obtain, because ectopic pancreas is hard to detect.…”
mentioning
confidence: 99%
“…Zhao et al . suggested that biopsy was useful for deciding on appropriate treatment for persistent umbilical discharge . For example, measuring the pancreatic enzymes in the liquid from the umbilicus may aid in diagnosis.…”
mentioning
confidence: 99%
“…В исследованиях Z. Zhao и соавт. [6] обнаружено, что лишь 14 из 60 обследованных пациентов были в возрасте до 18 лет, а подавляющее большинство -взрослые [6].…”
Section: Discussionunclassified
“…Основной метод верификации диагноза -гистологическое [2]. Не следует забывать, что эктопированная поджелудочная железа может стать причиной для малигнизации, исходящей из этой ткани [6,14]. Поэтому к этой группе пациентов следует относиться с онкологической настороженностью и полностью резецировать измененные отделы.…”
Section: Discussionunclassified
“…Heterotrophic tissue is also known to be associated with OMD remnants, particularly with Meckel’s diverticulum. This predisposes to local hyperacidity and mucosal ulceration, causing recurrent abdominal pain or per rectal bleeding in children [ 6 , 7 ]. Various surgical options have been described in the literature, ranging from wedge or segmental resection in case of Meckel’s diverticulum to umbilical exploration in case of umbilical discharge.…”
Section: Introductionmentioning
confidence: 99%